Knowledge and beliefs on antimicrobial resistance among physicians and nurses in hospitals in Amhara Region, Ethiopia - Abera, Bayeh (BioMed Central, 2014)
BACKGROUND: Antimicrobial resistance (AMR) is a major global public health problem both in hospital and community acquired infections. The present study assessed the knowledge and beliefs on AMR among physicians and nurses in 13 hospitals in Amhara region, Ethiopia, which is a low-income country. METHODS: A cross-sectional study using a self-administered questionnaire was applied. RESULTS: A total of 385 participants (175 physicians and 210 nurses) took part in the study. Sixty five percent of physicians and 98% of nurses replied that they need training on antimicrobial stewardship. Only 48% of physicians and 22.8% of nurses had exposures for local antibiogram data. Overall, 278 (72.2%) of participants were knowledgeable about AMR. Majority of participants agreed or strongly agreed AMR as worldwide and national problem but few considered AMR as problem in their own hospitals. The two most important factors mentioned for AMR development were patients’ poor adherence to prescribed antimicrobials (86%) and overuse of antibiotics (80.5%). The most leading local factors identified for AMR development were: self-antibiotic prescription (53.5%), lack of access to local antibiogram data (12.3%) and prescriber poor awareness about AMR (9.2%). Factors perceived for excessive antibiotic prescriptions were: patient drive (56%), treatment failure (79%), unknown febrile illnesses (39.7%) and upper respiratory tract infections (33.4%). CONCLUSION: Majority of physicians and nurses lack up to-date knowledge on AMR. Unavailability of local antibiogram data, self-prescription by patients and poor awareness on AMR are areas of interventions for prevention and control of AMR.